Estándares de calidad de aprendizaje en el área de ciencias naturales - Caisa Gavilema, Hector Anibal (2017)
The research project entitled "Learning Quality Standards in the area of Natural Sciences" was developed with the objective of diagnosing the development of skills and knowledge in the aforementioned area of students of the Fourth Year of Basic Education to evidence compliance with learning standards. The research problem has been formulated in the relationship between the development of performance- based skills and learning standards. The methodology used is exploratory, descriptive and explanatory, because the problem and the analysis of the causes with the result of the verification of the variables were studied. The research process has resulted in learning quality standards being descriptions of the learning achievements that students must achieve along the school path. Developing performance skills allows all students to have the same basic knowledge and skills in the area of Natural Sciences. Teachers do not apply performance criteria so students can not successfully meet learning standards. In addition, students focus on the importance of learning the natural sciences because they want to be promoted to the next school year, but not because they value the benefit of learning the natural sciences for their life. Therefore it is recommended to permanently socialize learning quality standards within educational institutions so that the entire educational community works to satisfactorily achieve the achievement indicators established for each educational level. Establish control mechanisms within the institution to evidence the development of the educational process based on skills with performance criteria.